Engineering of Exosomes to Target Cancer Metastasis - Zhenjiang Zhang; Jenna A. Dombroski; Michael R. King (2019)
Abstract As a nanoscale subset of extracellular vehicles, exosomes represent a new pathway of intercellular communication by delivering cargos such as proteins and nucleic acids to recipient cells. Importantly, it has been well documented that exosome-mediated delivery of such cargo is involved in many pathological processes such as tumor progression, cancer metastasis, and development of drug resistance. Innately biocompatible and possessing ideal structural properties, exosomes offer distinct advantages for drug delivery over artificial nanoscale drug carriers. In this review, we summarize recent progress in methods for engineering exosomes including isolation techniques and exogenous cargo encapsulation, with a focus on applications of engineered exosomes to target cancer metastasis.